Remagnetisation and magnetic refraction in proterozoic dykes from Central Scandinavia during Caledonian deformation - Wall, Helga de; Greiling, Reinhard O. (Physics and chemistry of the earth. Part A, Solid earth and geodesy, 2000)
Mafic dykes, related to the Central Scandinavian Dolerite Group, changed their geometry during the Caledonian orogeny from flat-lying bodies in the Autochthon to steeply inclined in the thrusted and stacked Lower Allochthon units. During tectonic transport a remagnetisation occured and the post-Jotnian paleomagnetic signature was completely obliterated. In the Bångonåive window this remagnetisation occurred at a deeper crustal level probably during metamorphism and deformation under amphibolite-facies conditions, while in the Børgefjell window it was caused by alteration in a more shallow crustal level. In both tectonic windows the remanence direction is influenced by the structure, and in the strongly anisotropic samples of the Bångonåinve window a distinct refraction of the remanence direction (up to 15°) towards the magnetic lineation is observed.